Regional haemodynamic effect of vasopressin infusion in conscious, unrestrained, Brattleboro rats. - Gardiner, S. M. (1989)
1. Incremental rates of infusion (0.027-4.0 pmol min-1) of exogenous vasopressin were given for 10 min periods to conscious, Brattleboro (i.e. vasopressin-deficient) rats, which had been chronically instrumented with pulsed Doppler probes and intravascular catheters (to permit assessment of regional haemodynamic changes). 2. There were no significant effects of the two lowest rates of infusion (0.027 and 0.105 pmol min-1) but, after 10 min of vasopressin infusion at 0.313 pmol min-1, superior mesenteric vasoconstriction had occurred unaccompanied by any other changes. Infusion of vasopressin at 0.687 pmol min-1 produced increases in blood pressure and in both mesenteric and hindquarters vascular resistance, but not change in renal vascular resistance or heart rate. These results do not indicate specific interactions between exogenous vasopressin and baroreflex mechanisms to offset the pressor effect of the neuropeptide. 3. The marked bradycardia, hypertension and renal, mesenteric and hindquarters vasoconstriction seen after 10 min infusion of vasopressin at 4.0 pmol min-1 were all abolished 10 min after administration of an antagonist of V1-receptors [+)-(CH2)5Tyr(Et)DAVP); additional antagonism of V2-receptors (with the non-selective antagonist (+)-(CH2)5Tyr(Et)VAVP) had no effects on any measured variable. Hence, the present experiments provide no evidence for important vasodilator effect of vasopressin in conscious, Brattleboro rats.